Development of Teaching Factory Model At Vocational High School (VHS) In Indonesia - Diana Nur Azizah; Supari Muslim; Ratu Noorita Achmad; Dhanu Lukmantoro; Umi Farida; Argo Ciptono; Joko Joko (Indonesian Journal of Learning Education and Counseling, 2019)
Vocational education has an important role in the effort to create a workforce that has competencies that are in accordance with the needs of the industrial world. But the open unemployment rate in Indonesia in February 2018 was 6.87 million people and 8.92% of them were graduates of VHS. Why does that much unemployment happen? Is the learning process at VHS not yet qualified, so that the quality of VHS graduates is still low? Can the teaching factory improve the quality of VHS graduates? To answer this question, research needs to be done. This research was conducted using literature studies on related references, and a number of research reports on teaching factories conducted at VHS and continued with FGD. The results of the study concluded that the teaching factory consisted of planning, organizing, implementing, and evaluating. The teaching factory developed was integrated with the production unit that was used for the practice of students, so that VHS graduates became qualified and ready to enter the workforce.